Open innovations for tourism logistics design: A case study of a smart bus route design for the medical tourist in the city of greater mekong subregion - Sumalee Ngeoywijit; Tawamin Kruasom; KiengKwan Ugsornwongand; Rapeepan Pitakaso; Worapot Sirirak; Natthapong Nanthasamroeng; Thachada Kotmongkol; Thanatkij Srichok; Surajet Khonjun; Chutchai Kaewta (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
One of the industries with the fastest growth rates worldwide, and notably in Thailand, is medical tourism. With connections to Cambodia and Laos, Ubon Ratchathani is located in lower northeastern Thailand, close to Vietnam and Myanmar. Therefore, there is a significant chance that this region will welcome medical travelers. High-quality medical facilities are available in Ubon Ratchathani to fulfill the needs of medical tourists. A visitor's decision to travel to Ubon Ratchathani for medical treatment is influenced by factors other than the high-level medical facilities, such as lodging, accessibility to public transportation, and tourist attractions. The public transportation services in Ubon Ratchathani, especially the public bus system, are poorly designed and may let down visitors. The purpose of this study is to develop a smart public bus route design that will meet tourists' demands. The concept of open innovation will be utilized to develop the model. We surveyed 400 visitors to Ubon Ratchathani. The tourists' opinions and views of public transportation will be made public and used as an input parameter when designing bus routes. The bus route can then be constructed using the differential evolution algorithm (DE). A web-based smart public transportation system was built. In order to construct an efficient smart public bus system (SPBS), open innovation was used in the development phase. According to the computational results, the new routes using DE lead to a 5.97% reduction in travel distance when compared to the output of the more well-known genetic method. More than 98.5% of visitors are satisfied with the new routes, and once they start running, 99.5% of all respondents plan to use public transit.
Keywords: 650; differential evolution algorithm; environmentally friendly; GPS monitoring; public transportation system; SMART bus system